Perspektif Antropologi tentang Komodifikasi Kearifan Lokal dalam Event Kota Makassar: Antara Pelestarian dan Pemanfaatan - Andi Try Haldyaqhza Syawaloedin HP; Darman Manda; Ahmadin Ahmadin (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2026)
This study analyzes the phenomenon of the commodification of local wisdom in various cultural events in Makassar from the perspective of cultural anthropology. The focus of the study is directed at how local culture is presented, negotiated, and utilized amid the interests of preservation and economics. The approach used in this research is descriptive qualitative, with data collection techniques carried out through field observations, in-depth interviews with various informants, and documentation. The data analysis was conducted using the theoretical framework of cultural representation and interpretation. The results of the study show that the representation of local culture in events tends to experience simplification in form, such as shortening the duration of performances, modifying movements, and adjusting visual elements to suit market and tourism demands. In addition, the findings also indicate that the commodification process produces two main connotations, namely the creation of economic opportunities for cultural actors and the risk of reducing the symbolic meaning and sacred values of a culture. Furthermore, there is a negotiation process between traditional values, economic interests, and the demands of modernity that reshapes the meaning of cultural authenticity within the context of events. Thus, the commodification of local wisdom in cultural events in Makassar is a complex phenomenon, as it simultaneously functions as a means of adaptive preservation and as a potential transformation of cultural meaning.